200k views
22 votes
6 / 32

Simplify
a)
4p + 2p – 3p
b)
9s- 5s + 2s-S
c)
8t + 3r - 76 - 9r​

User Esben Bach
by
5.6k points

2 Answers

4 votes

Answer: A) 3p , B) 5s , C) -6r+8t-76

Explanation:

A ) 4p + 2p – 3p

combine like terms :-

(4p+2p+-3p)

(4p+2p+-3p) = 3p

= 3p

B ) 9s- 5s + 2s-S

combine like terms :-

( 9s-5s+2s+-s)

( 9s-5s+2s+-s) = 5s

C ) 8t + 3r - 76 - 9r​

combine like terms :-

(3r+-9r)+(8t)+(-76)

= - 6r+8t+-76

User Rasheed
by
4.8k points
7 votes

Answer:

a.3p

b 5s

c 2r -76 this can be the answer

User Razvanc
by
6.0k points